2004
DOI: 10.1590/s0102-37722004000300003
|View full text |Cite
|
Sign up to set email alerts
|

Expectativas e sentimentos da gestante em relação ao seu bebê

Abstract: 3 Embora o presente estudo trate do período da gestação e do feto, o termo bebê foi usado em grande parte do texto, por parecer mais adequado ao se referir ao signifi cado que a mãe atribui ao fi lho ainda no útero. O termo feto é mais utilizado na literatura médica, mas parece não expressar adequadamente os sentimentos e as representações sobre o fi lho. Contudo, em algumas situações específi cas fez-se necessário recorrer ao termo feto para não confundir o leitor. RESUMO -A relação da mãe com seu bebê vai se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
91

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(103 citation statements)
references
References 9 publications
0
12
0
91
Order By: Relevance
“…This is further supported by the ART women's perceptions of fetal movements. Research on spontaneous pregnancy during the third trimester found that mothers referred to movements as bringing a feeling of satisfaction and happiness (Shahoei et al, 2011) or as a way to reinforce their influence over the baby, i.e., the movements were a response to what the mother was feeling (Piccinini et al, 2004). In contrast, for the current sample, it was the absence of movement, rather than the presence, that mattered.…”
Section: )mentioning
confidence: 54%
See 3 more Smart Citations
“…This is further supported by the ART women's perceptions of fetal movements. Research on spontaneous pregnancy during the third trimester found that mothers referred to movements as bringing a feeling of satisfaction and happiness (Shahoei et al, 2011) or as a way to reinforce their influence over the baby, i.e., the movements were a response to what the mother was feeling (Piccinini et al, 2004). In contrast, for the current sample, it was the absence of movement, rather than the presence, that mattered.…”
Section: )mentioning
confidence: 54%
“…Unsurprisingly therefore, concerns with the health of the baby, which are common among women with spontaneous conception during pregnancy (Melender, Lauri, 1999;Piccinini et al, 2004;Tsui et al, 2006;Shahoei et al, 2011), were also referred to by the majority of participants of this study. Fear of disease may have been heightened by the ART treatment experience, increasing expectant mothers' awareness of a newborn's physical vulnerability .…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…Segundo Piccinini, Gomes, Moreira e Lopes (2004), "a relação da mãe com seu filho já começa desde o período pré-natal, e se dá, basicamente, através das expectativas que a mãe tem sobre o bebê" (p.223). Além disso, essas expectativas são mais frequentes e intensas quando os movimentos do bebê anunciam sua existência real, fazendo com que a mãe sinta o feto e aumente suas expectativas referentes a ele.…”
unclassified